PHOTOVOLTAIC POWER SUPPLY OPTIMIZATION AND MODEL WITH ENERGY LOSSES CONSIDERATION - KHILCHUK, MYKOLA; HOLIAKA, ROMAN; KUKHTA, ROMAN; HALUSHKA, YEVHEN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The use of alternative power sources is one of the defining factors in the development of modern energy systems. The most efficient and advanced sources at present are energy generation systems based on photovoltaics. In addition to photovoltaic semiconductor components that primary convert light energy into electric current, secondary energy converters play a crucial role in photovoltaic systems. These converters manage the load circuits using pulse-based switching methods, relying on specialized controllers. The main method for optimizing the load of photovoltaic components is Maximum Power Point Tracking (MPPT). To implement the MPPT method, specialized control algorithms, controllers, and buck or boost converters are used.This work examines control modes for photovoltaic power systems that extend the MPPT method, taking into account the actual parameters of the converters, particularly the energy losses inherent to them. The scientific novelty of the proposed solutions lies in the optimization of the operating modes of photovoltaic sources, considering energy losses in MPPT converters. Using the example of the LT3495 boost converter, it is demonstrated that the energy efficiency of the converter significantly depends on the load current. Therefore, it is necessary to analyze the impact of load modes on energy losses in converters. Such an analysis is especially crucial when developing embedded systems for low-power electronic devices, particularly within the Internet of Things concept. Given that most parametric analyses of electronic circuits are conducted using SPICE models, this work develops a SPICE model for energy conversion in photovoltaic sources. The proposed model enables express analysis of the dependence of the power supply's energy efficiency on energy losses in MPPT converters and allows for adjustments in the energy extraction mode to maximize efficiency.
Keywords: photovoltaics; converter; controller; SPICE model